SISTEM INFORMASI PENJUALAN OBAT BERBASIS WEBSITE PADA PT BELIBIS MUDA PERKASA PALEMBANG MENGGUNAKAN FRAMEWORK LARAVEL - Humairoh, Nayu Nur; Yulianti, Evi; Alie, M. Fadhiel (Jurnal Ilmiah Informatika Global, 2025)
PT Belibis Muda Perkasa Palembang is a pharmaceutical distribution company that still employs manual methods in its sales processes. Sales representatives visit customers, such as pharmacies, hospitals, and drugstores, to offer products. Orders are placed through the sales team and manually recorded by the admin using physical invoices and Microsoft Excel. This process results in inefficiencies, susceptibility to recording errors, and challenges in real-time stock monitoring. This study aims to design a web-based sales information system to address these issues. Data collection methods include interviews, observations, and literature studies. The system is designed using the Laravel framework, MySQL database, and Agile development model. The proposed system is expected to allow customers to place orders independently at any time without waiting for sales visits. Additionally, it is designed to support automated sales reporting, improve recording accuracy, and enable real-time stock monitoring. By implementing this system, the company is anticipated to enhance operational efficiency and provide better accessibility for customers.